Eksistensi Badan Usaha Milik Desa Budi Rahardja Paska Undang-Undang Cipta Kerja - Ambarwati, Dewi; Assiddiq, Dafis Ubaidillah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
After the enactment of the Job Creation Law, BUM Desa experienced significant changes in the regulatory area regarding the legal status of BUM Desa which is regulated as a legal entity. This has implications for the management of BUM Desa in general, which must adjust to the new arrangements in the era of the Job Creation Law. Due to these changes, problems were found in the village sector, especially in Jambuwer Village, Kromengan District, Malang Regency, where there were several problems related to BUM Desa business management, aspects of liability and business risk mitigation. The research method used is empirical legal research using primary and secondary data. The result of this research is that several stages of socialization are needed regarding the legal aspects of BUM Desa business management and formulating the BUM Desa Standard Operating Procedure (SOP).